Analisis Strategi Bauran Pemasaran (Marketing Mix) Untuk Meningkatkan Daya Saing : (Studi Pada Saung Enggal) - Erfina Miftahul Jannah; Erika Adistia; Lilis Renfiana (Journal of Creative Student Research, 2023)
In the face of market dynamics, companies need to implement strategies to market their products effectively. The marketing mix with four main elements (product, price, place, and promotion) is a relevant strategy to implement. This research uses a qualitative research approach. The data sources used for this research are primary and secondary sources, which are obtained from interviews and observations at the Saung Enggal restaurant business. The purpose of this research is to find out the marketing mix strategy at Saung Enggal. The results of this study indicate that Saung Enggal has succeeded in increasing its competitiveness through a focused marketing mix strategy. In terms of products, attention continues to be paid to quality, updated menu design, wide variety, and strong brand management. Prices are set with consumer affordability in mind and in line with product quality. The strategic location in the center of community activities provides an advantage, supported by continuous efforts to improve access and facilities. Promotion is done through discounts and word-of-mouth strategies, with a focus on quality service and good customer relations. Overall, the implementation of the marketing mix successfully increased Saung Enggal's revenue by 2.9% from 2021 to 2022